2018
DOI: 10.3389/frobt.2018.00073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Robot Facial Characteristics and Gender in Persuasive Human-Robot Interaction

Abstract: The growing interest in social robotics makes it relevant to examine the potential of robots as persuasive agents and, more specifically, to examine how robot characteristics influence the way people experience such interactions and comply with the persuasive attempts by robots. The purpose of this research is to identify how the (ostensible) gender and the facial characteristics of a robot influence the extent to which people trust it and the psychological reactance they experience from its persuasive attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 82 publications
(144 reference statements)
2
63
0
Order By: Relevance
“…If the agent is a person, the attributes influencing the quality of interaction can be the length of the relationship (early encounters or later interactions), the character of the person, the aesthetics of the person (Dion et al, 1972), the degree of mutuality of his/her behavior. If the agent is a social robot, the characteristics influencing the quality of interaction can be the term of exposure to the interaction (i.e., short-term vs long-term), the social cues that the robot displays (Ghazali et al, 2017a and2018a), the language it uses (Ghazali et al, 2017a and2017b), its appearance (Wu et al, 2012;Wrobel et al, 2013;Ghazali et al, 2018b), the reciprocity of its behavior (Leite et al, 2014), and its contingent responsiveness (Díaz-Boladeras, 2017).…”
Section: Engagement With An Agentmentioning
confidence: 99%
“…If the agent is a person, the attributes influencing the quality of interaction can be the length of the relationship (early encounters or later interactions), the character of the person, the aesthetics of the person (Dion et al, 1972), the degree of mutuality of his/her behavior. If the agent is a social robot, the characteristics influencing the quality of interaction can be the term of exposure to the interaction (i.e., short-term vs long-term), the social cues that the robot displays (Ghazali et al, 2017a and2018a), the language it uses (Ghazali et al, 2017a and2017b), its appearance (Wu et al, 2012;Wrobel et al, 2013;Ghazali et al, 2018b), the reciprocity of its behavior (Leite et al, 2014), and its contingent responsiveness (Díaz-Boladeras, 2017).…”
Section: Engagement With An Agentmentioning
confidence: 99%
“…To limit the 'carryover effects' of the within-subject experimental design [52], the order of the three interactive social cues conditions was randomized for each participant. For instance, some participants interacted with the robot showing no interactive social cue in their first session, followed by the robot showing a high number of interactive social cues in their second session, and a robot showing a low number of interactive social cues in their last session.…”
Section: Participants and Designmentioning
confidence: 99%
“…More recently, special attention has been paid to the social responses to persuasive robots. Related research informs us regarding social responses to persuasive robots such as engagement, psychological reactance, trust and liking [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we can expect that users may have the interest to touch a robot or show affective response (such as highly engage) with a robot that makes them happy. Related studies [13,14,25] demonstrated how social cues displayed by robots could influence the affective responses toward persuasive robots. Persuasive robots with minimal social cues, for example, evoked less reactance compared to persuasive robots with enhanced social cues in a decision-making game [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation